MiR‐252 of the Asian tiger mosquito Aedes albopictus regulates dengue virus replication by suppressing the expression of the dengue virus envelope protein. Issue 8 (25th November 2013) - Yan, Hui; Zhou, Yanhe; Liu, Yanxia; Deng, Yuhua; Puthiyakunnon, Santhosh; Chen, Xiaoguang
Abstract The Asian tiger mosquito, Aedes albopictus is a major vector of dengue in mainland China. Dengue epidemics have spread from the southern coastal regions to the relatively northern and western regions since 1990s. Dengue has become an emerging public health problem in the southern coastal regions. microRNAs (miRNAs) are short non‐coding RNAs that regulate gene expression at the post‐transcriptional level. A highly abundant miRNA, miR‐252, was induced more than threefold after dengue virus serotype 2 (DENV‐2) infection in the Ae. albopictus C6/36 cell line. Transfection with miR‐252 inhibitor resulted in the increase of DENV‐2 RNA copies and the up‐regulation of DENV‐2 envelop protein (E protein) expression, whereas over expression of miR‐252 with its mimic decreased DENV RNA copies and the down‐regulation of E protein expression. MiR‐252 mimic reduced luciferase activity of a luciferase reporter that contained the predicted miR‐252 target on the DENV‐2 envelope gene sequence. The present results indicated that the miR‐252 of Ae. albopictus could regulate the gene expression of DENV‐2 E protein and may act as a cellular antiviral regulator in Ae. albopictus. J. Med. Virol. 86:1428–1436, 2014. © 2013 Wiley Periodicals, Inc.